Practical road safety auditing - Belcher, Martin (Thomas Telford, 2008)
This book explains the systematic process for checking the safety of new road schemes. Since the first edition in 2000 there have been many changes in the area of road safety auditing, such as the introduction of the new Road Safety Audit Standard.